(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Volodymyr Petrovych Filatov, an outstanding ophthalmologist, Academician of the AS of UkrSSR and AMS of USSR, and the founder of the Ukrainian ophthalmology school: a life pathway